Perceived utility of biological testing for autism spectrum disorder is associated with child and family functioning. (May 2020) - Yusuf, Afiqah; Peltekova, Iskra; Savion-Lemieux, Tal; Frei, Jennifer; Bruno, Ruth; Joober, Ridha; Howe, Jennifer; Scherer, Stephen W.; Elsabbagh, Mayada
Highlights: Integrating biomarkers into autism care pathways requires understanding the perceived utility of biological testing. Perceived utility of biological testing among parents increases with lower child functioning and higher family functioning. Child symptom severity, parent stress, and appraisal of family-centered care were not associated with perceived utility. Developing and integrating biological tests for autism requires systematic input from a representative sample of families. Abstract: Background: The clinical integration of chromosomal microarray testing promises improvements in diagnostic yields in Autism Spectrum Disorder (ASD). While the impact on clinical management is promising for some families, the utility perceived by families, including the majority for whom results are negative, is unclear. With next generation genomic sequencing technologies poised for integration, along with promising ASD biomarkers being developed, there is a need to understand the extent to which genomic and other biological testing would have utility for the target recipients of these tests and their families. The purpose of the present cross-sectional study was to examine the predictors of perceived utility of biological testing among parents of a child with ASD. Methods: The Perceived Utility of Biotesting (PUB) Questionnaire was developed based on literature review and integrating family review. Following their child's diagnosis, families participating in an ongoing prospective study completed the PUB questionnaire along with self-reported measures of parent stress, child and family functioning, and family-centered care prior to undergoing genetic testing for both clinical and research purposes. Results: Based on n = 85 families, psychometric properties of the Perceived Utility of Biotesting questionnaire suggest a reliable and valid instrument. A stepwise regression analysis reveals that lower levels of child emotional and behavioural functioning and higher levels of family functioning correlated with higher perceived utility for biological testing. Limitations: A main limitation in the study is the participation rate of 50 %, thus the possibility of self-selection bias cannot be ruled out. We also chose to assess perceived utility among parents rather than the individuals with ASD themselves: modifying the questionnaire to capture perceived utility from autistic individuals across the lifespan would prove essential in future studies. Finally, ongoing validation of the PUB by assessing the PUB's discriminant and convergent validity is still needed. Conclusions: We conclude that the utility of biological testing perceived by families whose child is undergoing genetic testing around ASD diagnosis depends on their unique child and family characteristics. This signifies that engaging families in biomarker discovery for improving the impact of research and care requires systematic input from a representative sample of families.